Spin‐Selective Generation of Triplet Nitrenes: Olefin Aziridination through Visible‐Light Photosensitization of Azidoformates. (6th January 2016) - Scholz, Spencer O.; Farney, Elliot P.; Kim, Sangyun; Bates, Desiree M.; Yoon, Tehshik P.
Abstract: Azidoformates are interesting potential nitrene precursors, but their direct photochemical activation can result in competitive formation of aziridination and allylic amination products. Herein, we show that visible‐light‐activated transition‐metal complexes can be triplet sensitizers that selectively produce aziridines through the spin‐selective photogeneration of triplet nitrenes from azidoformates. This approach enables the aziridination of a wide range of alkenes and the formal oxyamination of enol ethers using the alkene as the limiting reagent. Preparative‐scale aziridinations can be easily achieved under continuous‐flow conditions.